Uvod v pravo digitalnega enotnega trga in pravni vidiki servitizacije v EU: Študijsko gradivo - Hojnik, Janja (University of Maribor Press, 2025)
Introduction to Digital Single Market Law and Legal Aspects of Servitisation in the EU: Study Material. The European Union is modernizing its industrial strategy to enhance competitiveness and technological independence. A Digital Single Market is key to improving access to digital services, fostering innovation, and strengthening the resilience of European industry in the global market. Digital transformation also supports the development of artificial intelligence, quantum computing, and advanced communication infrastructures, crucial for the EU’s economic growth and strategic autonomy. This study material covers two main themes. The first part analyzes the legislative and strategic pillars of the Digital Single Market, focusing on geoblocking rules, cross-border VAT simplification, consumer protection, and platform regulation. It also examines key legislation such as the Digital Services Act, Digital Markets Act, and GDPR, as well as issues related to cybersecurity, data security, AI regulation, and copyright law. The second part explores servitisation, a megatrend enabling industrial transformation through digitisation. It shifts businesses from product sales to service solutions, increasing value and sustainability. Despite its relevance, servitisation remains overlooked in legal research and practice. The material concludes with questions and workshops that encourage critical analysis and discussion on the Digital Single Market’s legal and economic impact.